Kemampuan Komunikasi sebagai Pencapaian Tujuan Organisasi (Studi pada staf di STIKes Husada Jombang) - Setyowati, Risha; Kurniawan, Vendi Eko; Masyayih, Warda Anil; Anggraini, Rista Dian (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2025)
Background: Communication is a vital aspect of human activity and organizational processes, especially within higher education institutions. The effectiveness of internal communication directly influences the achievement of organizational goals. Objectives: This study explores the communication patterns at STIKes Husada Jombang and their impact on organizational performance. Methods: A qualitative approach using the Information System Approach theory was employed. Data were collected from staff at STIKes Husada Jombang through interviews and documentation of institutional practices. Results: Communication patterns were found to be highly personal and unstructured. Key issues included passive staff behavior, lack of follow-up on decisions, ineffective sanctions, and leadership that was not responsive to changes. These conditions hindered the achievement of the organization's vision and mission. Conclusion: Organizational goals at STIKes Husada Jombang are hindered by weak communication structures. Enhancing communication management is essential to foster innovation and organizational growth.